Mitochondrial and ER stress crosstalk in TBI: mechanistic insights and therapeutic opportunities - Wenzhe, Luo; Boyang, Xia; Yuchao, Gong; Bimcle, Riji; Yue, Yin (Frontiers in Cellular Neuroscience, 2025)
Traumatic brain injury (TBI) remains a major global public health concern, characterized by high morbidity, mortality, and long-term disability. Beyond the primary mechanical insult, the progression of secondary injuries—including neuroinflammation, oxidative stress, mitochondrial dysfunction, and excitotoxicity—plays a decisive role in long-term neurological outcomes. Emerging evidence positions cellular stress responses at the core of TBI pathophysiology, mediating the transition from acute injury to chronic neurodegeneration. This review systematically outlines the major stress phenotypes triggered by TBI, including oxidative stress, endoplasmic reticulum (ER) stress, mitochondrial distress, and autophagy imbalance. Particular emphasis is placed on the molecular interplay between the mitochondria and ER, where the mitochondria-associated membranes (MAMs) serve as dynamic hubs regulating calcium (Ca2+) homeostasis, ATP production, and apoptotic signaling. Disruptions in Ca2+ flux through MAMs exacerbate energy failure and promote reactive oxygen species (ROS) overproduction, triggering pro-inflammatory cascades and neuronal apoptosis. Furthermore, the crosstalk between ER-mitochondrial stress integrates signals that govern autophagy and inflammatory responses via key nodes such as C/EBP Homologous Protein (CHOP), Nuclear factor erythroid 2–related factor 2(Nrf2), and Nuclear Factor kappa-light-chain-enhancer of activated B cells (NF-κB). We also explore how stress crosstalk mechanistically contributes to neurological dysfunctions, including glial activation, axonal injury, and progressive cognitive-behavioral impairments. Understanding these intricate molecular mechanisms not only elucidates the pathogenesis of secondary brain damage but also unveils novel therapeutic targets for intervention. Targeting stress response integration may represent a transformative approach in preventing long-term disability and enhancing neuroregenerative outcomes following TBI.